Oral Complementary Medicine Use among People with Inflammatory Arthritis: An Australian Rheumatology Association Database Analysis. (5th June 2020) - Fletcher, Ashley; Lassere, Marissa; March, Lyn; Hill, Catherine; Carroll, Graeme; Barrett, Claire; Buchbinder, Rachelle
Abstract : Objectives . To describe oral complementary medicine (CM) use in people with inflammatory arthritis, associations with use, and changes in use over time. Methods . Demographic, clinical, and patient-reported outcome data from 5, 630 participants with rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PsA), and juvenile idiopathic arthritis (JIA) were extracted from the Australian Rheumatology Association Database (ARAD), a national observational database. CM use at entry into ARAD was ascertained for participants recruited between 2002 and 2018. CM was categorised according to the NIH/Cochrane schema (fatty acids, herbs, or supplements). Logistic regression was used to assess associations between demographic characteristics and CM use. Change in CM use between 2006 and 2016 was investigated using a nonparametric test for trend of rate by year. Results . 2, 156 (38.3%) ARAD participants were taking CM at enrolment (RA: 1, 502/3, 960 (37.9%), AS: 281/736 (38.2%), PsA: 334/749 (44.6%), and JIA: 39/185 (21.1%)). CM use was more prevalent in women (OR 1.3; 95% CI: 1.13-1.50), those with tertiary education (OR 1.32; 95% CI: 1.13-1.55), private health insurance (OR 1.26; (95% CI: 1.10-1.44), drinking alcohol sometimes (OR 1.22; 95% CI: 1.05-1.43), poorer function (HAQ) (OR 1.13; 95% CI: 1.02-1.24), use of NSAID (OR 1.32; 95% CI 1.17-1.50), weak (OR 1.21; 95% CI 1.05-1.41) but not strong opioids, and less prevalent in current smokers (OR 0.76; 95%: CI 0.63-0.91). CM use was not associated with pain, disease activity, or quality of life. The most common CMs were fish oils (N = 1, 489 users) followed by glucosamine (N = 605 ). Both declined in use over time between 2006 and 2016 (27.5% to 21.4%, trend p = 0.85 and 15.5% to 6.4%, trend p < 0.01 ), respectively. Conclusion . Oral CM use is common among Australians with inflammatory arthritis. Its use is greater among women and those with tertiary education. Fish oil and glucosamine, the most common CMs, both declined in use over time.